Individual liaison: Gregorius Sidharta, tradition, and modernity - Gumilar, Ganjar (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
Understanding the dialogic relation between tradition and modernity in our current cultural dynamic remains an ‘incomplete project’ that requires careful examination. Approaching and thoroughly interpreting both roles in our society, mainly in how they influenced our current paradigm of culture, continue to pose risks and challenges. This article will explore the works of Gregorius Sidharta Soegijo, a renowned maestro of Bandung modern art, whose conversational practice proposes a particular means of harmonizing these antagonistic tensions and various derivatives issues that might later follow. By using art criticism as its primary modalities while simultaneously cross-referencing both modern and contemporary aesthetic paradigms, this article will demonstrate how Sidharta’s inclusive and deliberate approach might provide a dialogic site for various antagonist polarities—mainly tradition and modernity—to coexist within a democratic, horizontal, and productive axis. His audacity in contemplating inward and resorting to his idiosyncrasy would also be highlighted for its contributive nature as the pretext of his attempt to reconcile, resolve, and synthesize the long-desirable harmony between tradition and modernity. These gestures have undergone a consistent, gradual process of internal reflection that touched upon his personal experiences, particularly his encounter with multitudes of cultural values, perspectives, and paradigms that each proposes their significance.